Crusaders, monks and family fortunes: evolutionary models of male homosexuality and related phenomena - Tureček, Petr; Fořt, Jakub; Flegr, Jaroslav (Proceedings. Biological sciences, 2025)
The fraternal birth order effect (FBOE) is a well documented preponderance of older brothers among gay men. Until now, it has lacked a proper formal treatment in light of evolutionary theory. In this article, we propose two related mathematical models based on the rigorous application of the inclusive fitness concept. The models examine sibling rivalry and resource allocation within families. One of the models assumes that the laterborn's reproductive ability is not compromised by the manipulation that leads to the exclusive allocation of family resources to the firstborn. The other model posits that this manipulation may lower the laterborn's direct fitness to zero. Both models suggest that the FBOE arises primarily from the older brother's manipulation, as the firstborn's inclusive fitness may increase, while the mother's decreases, but not vice versa. However, under certain conditions, the mother should support an activity that discourages division of family resources, and in extreme cases, the younger brother's homosexuality may be the best available reproductive strategy for his genes. The models also provide insight into the cultural evolution of primogeniture and explain how manipulation between relatives could evolve before the emergence of substantial economic inequality.
Keywords: fertility; Siblings; inclusive fitness; pořadí narození; evolution; Male; sourozenci; lidé; biologická evoluce; mužské pohlaví; fraternal birth order effect; Homosexuality, Male; Biological Evolution; homosexuality; Humans; homosexualita mužská; Birth Order; manipulation